DEIKSIS DALAM FILM A WALK TO REMEMBER KARYA ADAM SHANKMAN (ANALISIS PRAGMATIK) - PALUPI, IIN INDAH; KODONG, FENTJE; MANUS, JEANE ANGELA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTThis research entitled â€œDeiksis Dalam Film A Walk To Remember Karya Adam Shankman: Suatu Analisis Pragmatikâ€. The statements of problem of this research are: what are the types of deixis in film A Walk to Remember by Adam Shankman? and how is the use of deixis in film A Walk to Remember by Adam Shankman?. The objectives of this research are to identify and classify the types of deixis and to analyze the use of deixis in the film A Walk to Remember by Adam Shankman. This research used a descriptive method. The data of deixis collected from the sentence in conversation from the characters in the film and analyzed according to Levinsonâ€™s theory (1983).The result of this research shows that there are five types of deixis in the film A Walk to Remember, those are person deixis (first person: I, my, me, mine, we, our; second person: you, your, yours; third person: he, him, she , her), place deixis: here, there, inside, time deixis: today, tomorrow, 2 years ago, right now, tonight, 4 years, discourse deixis: this, that, these, social deixis: sir, reverend, son, father, child, husband, wife, citizen high, citizen low. The use of deixis found in the film A Walk to Remember are gestural usage and symbolic usage.Â Â Â Â Â Â Â Â Â Â Â Keywords: Deixis, Pragmatic, Film: A Walk to Remember